(untitled) (Marketing Journal, 2025)
The article scientifically substantiates the relevance, causes, and consequences of assessing interregional inequalities in the Republic of Uzbekistan. The intensification of regional imbalances more clearly highlights the disruption of balance between the advantages and challenges associated with decentralization policy and local self - government. The research considers regional disparities as factors negatively impacting population welfare, economic activity, and opportunities for utilizing labor potential, thoroughly analyzing the economic -geographical and ecological specificities of Uz bekistan. Additionally, issues such as inherited uneven economic development, concentration of production and investments, and the formation of an “enclave” economy in certain regions are scientifically examined. The author emphasizes that the aim of regio nal policy is not to equalize but strategically leverage existing disparities to achieve positive outcomes, providing relevant theoretical and practical recommendations.